2023
DOI: 10.3390/app13105955
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Mechanical Properties and Deterioration Mechanism of Red Sandstone from the Panjiatuo Landslide under Action of Acidic Drying−Wetting Cycles

Abstract: Due to frequent water level fluctuations and complex hydrochemical environments, rock slopes in reservoir areas progressively deteriorate and become unstable. This study investigated the coupling effect of drying−wetting cycles and acidic solutions on the physical and mechanical properties, strain field evolution, failure mode, and micro-mechanism of red sandstone using a series of laboratory experiments (wave velocity tests, uniaxial compression tests, the digital image correlation method, scanning electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…However, when testing the initial ultrasonic velocity of the specimens, it was found that there were differences in the ultrasonic data obtained, even for the same type of specimen. Therefore, to facilitate the analysis of ultrasonic variation, the ultrasonic velocity was normalized [34,35]. The normalized ultrasonic velocity is defined as V ijB , and the ultrasonic velocity obtained from the nth wet and dry cycle of specimen number j in group i during the wet and dry cycle test is Vij(n).…”
Section: Change Rule Of Ultrasonic Velocity In Red Sandstone Specimensmentioning
confidence: 99%
“…However, when testing the initial ultrasonic velocity of the specimens, it was found that there were differences in the ultrasonic data obtained, even for the same type of specimen. Therefore, to facilitate the analysis of ultrasonic variation, the ultrasonic velocity was normalized [34,35]. The normalized ultrasonic velocity is defined as V ijB , and the ultrasonic velocity obtained from the nth wet and dry cycle of specimen number j in group i during the wet and dry cycle test is Vij(n).…”
Section: Change Rule Of Ultrasonic Velocity In Red Sandstone Specimensmentioning
confidence: 99%